Activation and active labour market policies in OECD countries: Stylized facts and evidence on their effectiveness - John P. Martin (Institute for the Study of Labor (IZA), 2014)
Activation policies aimed at getting working-age people off benefits and into work have become a buzzword in labour market policies. Yet they are defined and implemented differently across OECD countries and their success rates vary too. The Great Recession has posed a severe stress test for these policies with some commentators arguing that they are at best "fair weather" policies. This paper sheds light on these issues mainly via the lens of recent OECD research. It presents the stylized facts on how OECD countries have responded to the Great Recession in terms of ramping up their spending on active labour market policies (ALMPs), a key component in any activation strategy. It then reviews the macroeconomic evidence on the impact of ALMPs on employment and unemployment rates. This is followed by a review of the key lessons from recent OECD country reviews of activation policies. It concludes with a discussion of crucial unanswered questions about activation.
Keywords: J01; J08; J68; 330; activation; active labour market policies; Great Recession; unemployment insurance; benefit conditionality